2008
DOI: 10.2320/matertrans.mra2007267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milling on the Carbothermal Reduction of Oxide Mixture for (Ti,W)C-Ni

Abstract: The effect of high-energy milling on the phase transformation and carbothermal reduction was examined using an oxide mixture, TiO 2 -WO 3 -NiO-C, with a process to synthesize (Ti,W)C cermets. Due to the high energy involved in the mill raw, anatase TiO 2 transformed first to TiO 2 -II and then to rutile, while WO 3 transformed to a high-pressure WO 3 -HP and hexagonal WO 3 phase. The co-existence of WO 3 and TiO 2 enhanced the formation of a nano-crystalline or amorphous phase. The (Ti,W)C phase was formed mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…[3][4][5][6][7][8] The synthesis of (Ti,W)(CN) powders, through high-energy ball milling and carbothermal reduction of oxide mixtures, is well described elsewhere. [9][10][11][12] The presence of the metallic phase, which was introduced from the milling media, enabled the densification of (Ti,W)(CN) at low temperatures without external pressure.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] The synthesis of (Ti,W)(CN) powders, through high-energy ball milling and carbothermal reduction of oxide mixtures, is well described elsewhere. [9][10][11][12] The presence of the metallic phase, which was introduced from the milling media, enabled the densification of (Ti,W)(CN) at low temperatures without external pressure.…”
Section: Introductionmentioning
confidence: 99%
“…1a shows that the oxide phases remained, and were not converted completely to carbide after reduction heat-treatment at 1300 C. When ZrO 2 is carbothermally reduced, intermediate phases, such as ZrO and Zr 2 O, are evident during the reduction process. ZrO 2 is expected to be converted to ZrO, then to Zr(CO), and finally to ZrC in a similar way to that previously observed for TiO 2 [29,30]. Complete carburization of ZrO 2 requires high temperatures (as shown in Fig.…”
Section: In Situ Wezrc and Wezr(cn) Powder Synthesismentioning
confidence: 74%
“…As mentioned in the previous section, the (1 0 1) prism plane develops preferentially in (W 0.9 Ti 0.1 )C powder, which serves as a base for the thin platelet morphology. Our previous studies [18,19] reported that WC forms between 600 and 800 • C from milled mixtures of WO 3 and C, while TiC forms around between 1000 and 1200 • C from milled mixtures of TiO 2 and C. Therefore, it is more likely that (W,Ti)C is expected to form first at a low temperature and followed by the (Ti,W)C formation (between 1000 and 1200 • C). This view is supported by the XRD results in Fig.…”
Section: Platelet Formation In (W 1−x Ti X )C-co Cermetsmentioning
confidence: 92%